Osteolytic lesions as the sole presenting feature of secondary syphilis. Issue 6 (22nd June 2021) - Colquhoun, Matthew; Kirresh, Othman; Keikha, Mohammad; Haddow, Lewis
Abstract : We present the case of a 48-year-old man with a background of well-controlled HIV who presented with bony pain in multiple regions and raised inflammatory markers. After an investigative process, the patient was newly diagnosed with secondary syphilis. Bony pain, secondary to osteolytic lesions and demonstrated on plain radiography, CT and nuclear medicine imaging, was the sole presenting feature. The patient was successfully treated with penicillin G and his symptoms improved. Rheumatologists are often tasked with diagnosing the cause of a patient's pain. However, in this case, a multidisciplinary approach was needed and the contribution of a specialist in Genitourinary Medicine/HIV was required to help diagnose this rare cause of bony pain.